Parenting Patterns for Dreadlocked Children: A Local Culture-Based Study among Muslim Farmers in Dieng, Wonosobo - Munawaroh, Hidayatu; Arif, Mahmud; Soehadha, Moh (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Local traditions play a pivotal role in shaping parenting practices and early childhood development in rural Indonesian communities. This study explores the beliefs, values, and daily parenting practices surrounding dreadlocked children at an early age within Muslim farming families in Dieng, Wonosobo. Employing an ethnographic qualitative design, the research investigates how Islamic teachings and local traditions intersect to shape caregiving patterns for children aged 2–7 whose dreadlocks are perceived as sacred signs of spiritual and ancestral connection. Data were collected through participatory observation, in-depth interviews, focus group discussions, document analysis, and life history narratives with 25 key informants including parents, kyai, and community elders. Findings reveal that dreadlocked children are regarded as culturally blessed, with parenting approaches characterized by emotional attentiveness, permissiveness, and ritualized social inclusion. The practice of ruwatan—a ceremonial haircut accompanied by prayers and offerings—emerges as a key event in cultural learning and early character development. These parenting patterns reflect a model of culturally responsive education that emphasizes identity formation, moral values, and communal integration. The implications underscore the necessity of redefining special needs education to accommodate culturally distinct child-rearing practices. However, as the study is context-specific and based on qualitative methods, its findings require further exploration through comparative and longitudinal research. The research contributes to a growing discourse on inclusive and localized approaches to early childhood education in multicultural societies